Influence of second oder aberrations on mass-separation with 270° analyzing magnet - Dolinskii, A.; Dolinska, M.; Valkov, A.; Gorda, A.; Rudenko, T. (Вопросы атомной науки и техники, 2008)
In this paper we study nonlinear characteristics of the wide aperture dipole magnet CP-17, which is utilized as an analyzing magnet in the stable isotope separator of the INR (Institute for Nuclear Research) in Kiev. A brief theory of the second order aberration of the magnetic field is outlined. Based on this theory numerical calculations have been performed to study the achievable power resolution depending on nonlinear magnetic field and on beam parameters.